2013
DOI: 10.5005/jp-journals-10021-1208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Optimal Implant Positions and Height of Retraction Hook for Intrusive and Bodily Movement of Anterior Teeth in Sliding Mechanics: A FEM Study

Abstract: Introduction:The design of an appliance for retraction of six anterior teeth using orthodontic mini-implant (OMI) anchorage and sliding mechanics must take into account the position and height of the mini-implant and the height of the anterior retraction hook, we used finite element analysis to examine effective en masse retraction with orthodontic mini-implant anchorage and sought to identify a better combination of the above factors.Materials and methods: Base models were constructed from a measurements give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…The force levels passing from the high pull implant to the retraction hook will cause intrusion and from the medium pull implants shows bodily movement and low pull implant showed tipping forces. A study conducted by Shrinivas S Ashekar et al [39] suggest that the force levels passing from the high pull implant to the retraction hook will cause intrusion and from the medium pull implant shows bodily movement and the low pull implant showed tipping forces which supports the present study. So, the high pull implants show high intrusive effect, and the canines showed extrusion in all cases as the retraction force is more towards the canine as the tipping of the canines is observed.…”
Section: Discussionsupporting
confidence: 87%
“…The force levels passing from the high pull implant to the retraction hook will cause intrusion and from the medium pull implants shows bodily movement and low pull implant showed tipping forces. A study conducted by Shrinivas S Ashekar et al [39] suggest that the force levels passing from the high pull implant to the retraction hook will cause intrusion and from the medium pull implant shows bodily movement and the low pull implant showed tipping forces which supports the present study. So, the high pull implants show high intrusive effect, and the canines showed extrusion in all cases as the retraction force is more towards the canine as the tipping of the canines is observed.…”
Section: Discussionsupporting
confidence: 87%
“…Chetan et al 17 showed retraction component of force reduces by around 1% and the intrusion component of force increases by around 0.3% for each millimeter apical placement of the screw. Ashekar et al 16 proved that low mini-implant placement (6 mm) causes anterior teeth to tip, mid-implant placement (8 mm) causes bodily movement, and high implant placement (10 mm) shows intrusion in the FEM model. The ideal height for the bilateral implant position for the retraction of the anterior teeth is 10 mm 20 .…”
Section: Position Of Mini-screwmentioning
confidence: 99%
“…Zhang et al, 13 Sung et al, 14 Kojima et al, 15 Ashekar et al, 16 Chetan et al, 17 Hedayati et al, 19 Namburi et al, 20 Bohara et al, 23 and Suzuki et al 24 used ANSYS software for simulation, whereas Jain et al have not mentioned the software used for the study. Kojima et al, 15 Suzuki et al, 24 and Parashar et al 18 designed an FEM model based on the CT scan and converted it into a 3D model, while other studies such as Ashekar et al, 16 Chetan et al, 17 and Hedayati et al 19 designed a model based on Wheeler's dental anatomy textbook. Jain et al 22 and Bohara et al 23 did not quote the model design.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 2 more Smart Citations